Silver Economy in China: Conceptual Evolution, Structural Challenges, and Development Pathways - Zhang, Kaibo (Journal of Global Economy, Business and Finance, 2026)
The silver economy has emerged as a strategic priority in China’s response to rapid population aging, representing both a significant economic opportunity and a complex policy challenge. This paper provides a comprehensive analysis of the conceptual evolution, current landscape, and structural contradictions of China’s silver economy. Drawing on policy analysis and empirical evidence, we examine four critical dimensions: the conceptual framework distinguishing silver economy from traditional notions of elderly care; the supply-side dynamics characterized by market growth alongside structural imbalances; the demand-side constraints rooted in pension adequacy and consumption psychology; and the technological dimension where AI-driven innovation meets implementation challenges. Our analysis reveals that while China’s silver economy has reached approximately 7 trillion yuan in 2025 and is projected to grow to 30 trillion yuan by 2035, it faces fundamental structural contradictions including policy fragmentation, supply-demand mismatches, and the coexistence of excess capacity and unmet needs. We argue that realizing the silver economy’s potential requires systematic policy integration that balances welfare provision with market development, bridges the digital divide through inclusive design, and fosters institutional mechanisms for sustainable industry growth. The findings contribute to both theoretical understanding of aging economies and practical policy formulation for navigating demographic transition.